EU Role in the Republic of Moldova European Integration Within Eastern Partnership - Cristina Morari (CES Working Papers, 2016)
The article presents an analysis of the role of European Union in the European integration process of the Republic of Moldova in the context of Eastern Partnership and it was supported by a Marie Curie International Research Staff Exchange Scheme Fellowship within the 7th European Community Framework Programme. The European integration of the Republic of Moldova is a complex process that implies external and internal efforts, but internal transformations generated by this process are determined primarily by the EU initiatives. This fact is based on both, the necessity of the Republic to correspond to European norms and the EU interest to have reliable and stable partners from economic and political point of view. The Association Agreement, DCFTA, visa liberalization are main bonuses that Moldova has received from EU within Eastern Partnership. At current stage, EU continues to play an important role in domestic transformation and stabilization of the country, by providing assistance and consultation. The interdisciplinary approach and methods as analysis of official documents, comparison and observation gave the possibility to estimate the level and results of how EU establishes and influences both, the agenda of European integration and domestic transformations of the Republic of Moldova.
Keywords: F5; 330; Eastern Partnership; EU; Republic of Moldova; European integration; Association Agreement; conditionality